Epimeria liui sp. nov., a new calcified amphipod (Amphipoda, Amphilochidea, Epimeriidae) from a seamount of the Caroline Plate, NW Pacific - Wang, Yanrong; Zhu, Chaodong; Sha, Zhongli; Ren, Xianqiu (ZooKeys, 2020)
A calcified individual of Epimeria Costa, 1851 collected from an unnamed seamount of the Caroline Plate, NW Pacific, is recognized as new to science herein. This increases the number of known Epimeria species of the North Pacific to nine. Epimeria liui sp. nov. differs from its similar congeners by having a rostrum hardly reaching to the end margin of first peduncular article of antenna 1, the presence of large pyriform eyes, the size-increasing mid-dorsal teeth starting from pereonite 6 to pleonite 2, the projection on coxa 5 not extending to epimeral plate 1, and by having a nearly quadrate telson notched medially. To facilitate identification the new species is included in a key to Pacific species of Epimeria .